Enforcement of alternative measures to detention in EU countries: The Italian situation - Cali, Monica (European journal of probation, 2024)
With Framework Decision 2008/947/JHA, about the application of the ‘principle of mutual recognition to sentences and probation decisions with a view to the supervision of probation measures and alternative sanctions’, the European legislator intervened on the matter of criminal enforcement in order to coordinate those cases in which an ‘alternative sanction’ is issued in one country and executed in a foreign country. This regulatory act, in addition to allowing the implementation of some founding principles of the European Union – in particular the mutual recognition of judicial decisions as well as the freedom of residence and movement in the various member countries – also pursues the express aim of ‘strengthen the possibility of social reintegration of the convicted person, allowing him to maintain, among other things, family, linguistic and cultural ties, but also to improve the control of compliance with the probation measures and alternative sanctions with the aim of preventing recidivism, taking therefore consideration to the protection of victims and to the public, generally’.